Pengaruh Intensitas Modal, Tingkat Hutang, dan Cakupan Biaya Tetap Terhadap Tarif Pajak Efektif - Iis Stikhomah Tanjung; Luh Nadi (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2024)
This research aims to determine and test empirically the influence of Capital Intensity, Debt Equity Ratio and Fixed Cost Coverage on Effective Tax Rates. The data used in this research is secondary data. This research uses a sample of companies in the Primary Consumer Goods (Consumer Non-Cyclicals) sector listed on the Indonesia Stock Exchange in 2018 - 2022. The number of samples in this research is 33 companies with a research year of 5 years, so the total sample is 165 data. This research uses a purposive sampling method. The total sample for this research is 33 financial reports. The data analysis techniques used are descriptive statistical analysis, panel data regression model estimation, panel data regression model selection techniques, classical assumption tests, multiple linear regression analysis, hypothesis testing, and coefficient of determination with the help of the Eviews 9 program. Capital Intensity, Debt Equity Ratio and Fixed Cost Coverage simultaneously influences the Effective Tax Rate. Partially, Capital Intensity influences the Effective Tax Rate. Debt Equity Ratio have no effect on Effective Tax Rates. Fixed Cost Coverage influences the Effective Tax Rate.